The implementation of Quizizz-based online evaluation in higher education: An exciting alternative for evaluation - Muji, Anggarda Paramita; Ambiyar, Ambiyar; Aziz, Ishak; Hidayat, Hendra (International Journal of Research in Counseling and Education, 2021)
The challenges of online learning during the Covid-19 pandemic require creativity and learning innovation, so online learning evaluation is very much needed. The purpose of this paper is to explore the implementation of Quizizz-based online evaluation in universities as a fun alternative to evaluation. Quizizz has adequate features to serve as a means of evaluating online learning such as quizzes and daily assessments. However, most of them only use Quizizz as a learning game, whereas through Quizizz various formal learning evaluations can be carried out such as quizzes, daily assessments, surveys and so on. This research method is a qualitative method. Methods of collecting data with literature review, observation, and interviews. Sampling was selected by purposive sampling method, There are 56 students from the class of 2021 who are taking electronic components lectures, of which 21 are male and 35 are female, ranging in age from 19 to 20 years. The results of the study found that the implementation of Quizizz is easy to use, has many features and many facilities that support learning evaluation activities. Furthermore, the use of features on Quizizz, such as Live Quiz, gives the impression of live evaluation which is fun. Learning evaluation through Quizizz can make it easier for lecturers to make detailed and objective assessments. So, with the current Covid-19 pandemic, learning evaluation with Quizizz is the right alternative.